HUBUNGAN SELFCARE DENGAN KUALITAS HIDUP PASIEN DIABETES MELLITUS DI WILAYAH KERJA PUSKESMAS RASIMAH AHMAD KOTA BUKITTINGGI TAHUN 2022 - Yossi Fitrina; Dona Amelia; Jihan Fadhilla (Jurnal Kesehatan Saintika Meditory, 2022)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both. Quality of life of patients with diabetes mellitus on average have a poor quality of life due to physical changes caused by increased blood sugar levels. One way to improve the quality of life is good self-care. The purpose of this study was to identify the relationship between Selfcare and Quality of Life of Diabetes Mellitus Patients in the Work Area of Rasimah Ahmad Public Health Center, Bukittinggi City in 2022. This research method used quantitative research with a cross sectional design. The population of this study were all people with Diabetes Mellitus in the Work Area of the Rasimah Ahmad Health Center, Bukittinggi City in 2022 with a total sample of 110 people. The research instrument was a self-care questionnaire (SDSCA) and a quality-of-life questionnaire (DQOL). Analysis of the data using the Spearman-rank test with (p = 0.000 < 0.05). The results showed that there were 43 respondents (39.1%) with sufficient self-care category, and 46 respondents (41.8%) with moderate quality of life. The conclusion is that there is a relationship between self-care and the Quality of Life of Diabetes Mellitus Patients in the Work Area of the Rasimah Ahmad Public Health Center, Bukittinggi City in 2022. Based on the results of previous research, the authors realize that there are still many limitations and errors in this study. However, this research is expected to make a useful contribution.  Keywords: Diabetes Mellitus, self care, quality of life Reading list: (2012-2022).